Contribution of genetics to hematopoietic stem cell mobilization: a genome-wide association study of 564 healthy donors mobilized with granulocyte colony-stimulating factor - Miriam Stenzinger; Susanne Beck; Iordanis Ourailidis; Anna-Lena Volckmar; Nagarajan Paramasivam; Aysel Ahadova; Aitzkoa Lopez de Lapuente Portilla; Phuong La Yen; Bjorn Nilsson; Justo Lorenzo Bermejo; Halvard Bonig; Jan Budczies (Haematologica)
Hematopoietic stem and progenitor cells (HSPC) from mobilized blood are the preferred graft source for allogeneic and autologous stem cell transplantation. The efficiency of CD34+ cell mobilization with granulocyte colony-stimulating factor (G-CSF) varies significantly between individuals, but is reproducible across mobilization cycles within an individual, suggesting a genetic component, a hypothesis that has been previously investigated by testing for candidate single-nucleotide polymorphisms (SNP) associations. As the genetic determinants of HSPC mobilization have not been analyzed on the genomic scale so far, we performed a genome-wide association study (GWAS) in a German population of 564 healthy G-CSF mobilized allogeneic stem cell donors.